Investigation on the Performance in Tire Repair Operation – A Case Study for Semi Automation in MSMEs - Maidawati; Purnama, Adji; Mahendrawan, Sidik (Jurnal Teknologi, 2024)
This investigation involved Micro, Small, and Medium Enterprises (MSMEs) specializing in tire repair services. The conventional methods employed by tire patchers using manual tools with heating systems fueled by gasoline, kerosene, or spirit have raised concerns regarding safety, as they are prone to fire hazards. In response to these challenges, some tire repairs have adopted modern tire patching devices equipped with electric heating systems, which not only demand lower electric power but also offer enhanced safety features. The utilization of electric heating systems in modern tire patching devices not only addresses safety concerns but also contributes to the overall improvement of patch quality. The electric heating systems are designed to provide a controlled and measurable amount of heat, ensuring a more robust adhesion of tire patches and, consequently, a higher quality repair. The objective of this report is to advocate for the optimization of tire repair performance through the implementation of tire patching process semi automation. The result shows that by applying semi automation, MSMEs in the tire repair can enhance the efficiency of the patching process, and significantly reduce safety risks associated with traditional heating methods. This optimization contributes to a safer working environment but also leads to a more sustainable and higher in quality of tire repair service.